รูปแบบการพัฒนาด้านความปลอดภัยและ สิ่งแวดล้อมของโรงเรียนเครือข่าย มหาวิทยาลัยอุบลราชธานี อำเภอวารินชำราบ จังหวัดอุบลราชธานี - หลาบคำ จิราภรณ์; บุญขาว ลักษณีย์; ชาคำรุณ นิตยา; ทองดำ สมเจตน์; ทิพย์พิลา จีราพร; ศิริบูรณ์พิพัฒนา จินตนา (Area Based Development Research Journal, 2015)
บทคัดย่อไม่สมบูรณ์ The development of pattern of safety and environmental management for Ubon Ratchathani University’s School Network, Warinchamrap District, Ubon Ratchathani Province The objectives of this research were 1) to study the problems of safety and environmental management of the sampling school 2) to study availability of safety and environmental management of the sampling school 3) to search for the suitable pattern of safety and environmental management of the sampling school. The research was based on processes and activities that involved the community participation, and the exchange learning between the research team. The research methodology consisted of the full participatory in every step; the generation of research question, the creation of research tools, the collection of data, the analysis and synthesis of data. The results of safety management problems for the playground management were as follows; full of high grass in the playground, uneven floor, solid ground, damaged, rusty, and unsafe play instruments. For environmental management problems including 1) waste management-insufficient trash in school, trash damaged, unlidded and unclassified container and 2) food sanitation-physical environment of the cafeteria did not meet the standards of the Department of Health for 8 items; contaminated with coliform bacteria on the hands of all handlers and all food samples. Regarding school readiness on this issues, all three schools has different readiness of safety and environmental management in three area; solid waste management, food safety and the playground arrangement. From the processes of participatory action research, the searching for the appropriate pattern of safety and environment development for Ubon Ratchathani University’s school network can be done through 1) the increasing of the perception of safety and environmental problems in school 2) the encouraging about the awareness of the health impact of safety and environment in school 3) the reflecting on the schools’ potential and readiness in improving the safety and environmental management in school and 4) the creation of mechanisms for sustaining the effective management of safety environment in school.